An evaluation and prioritisation of conflict resolution procedures arising in the implementation of sustainable development - Macfarlane, Ian(Ian Richard) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Phil.) -- University of Stellenbosch, 1997.